The Acquisition of Pragmatic Competence in Indonesian Abroad Programs: The Importance of Informal Indonesian - Suwarno, Peter (PAROLE: Journal of Linguistics and Education, 2018)
This paper presents some comparisons between speeches of advanced learners of Indonesian with those of the native speakers, which indicates that many advanced learners do not communicate the way native speakers usually do. This can be attributed to the Indonesian language programs that focus mostly on teaching formal Indonesian grammar and vocabularies, neglecting informal conversational Indonesian which is essential for the acquisition of pragmatic competence. This paper discusses the importance of pragmatic competence in Indonesian language learning, including learning various speeches commonly used in daily interactions. Based on recordings of learners’ interactions as well as notes on observations of teaching-learning activities in selected Indonesian abroad programs, this paper describes the challenges of developing pragmatic competence based on examples of learners’ non-grammatical errors as well as inappropriate interactional uses of Indonesian. In addition, this paper will explain issues and challenges of achieving pragmatics competence in these programs and suggests possible solutions.